PENERAPAN MODEL PBL DENGAN PENDEKATAN CRT UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN PANCASILA MATERI GOTONG ROYONG KELAS IV SD N LAMPER LOR - kusumawati, anyta; Sari, Yunita; Ulia, Nuhyal (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to improve student learning outcomes in the Pancasila Education subject of class IV of Lamper Lor State Elementary School through the application of the Problem Based Learning (PBL) model with the Culturally Responsive Teaching (CRT) approach. This study uses Classroom Action Research (CAR) with two cycles. The instruments used include learning outcome tests, student activity observation sheets, and documentation. The subjects of this study were class IV students consisting of 26 students. The results of this study showed an increase in the average value of student learning outcomes, namely from 20% of students who achieved completeness in the pre-cycle, increasing to 40% in cycle I, and reaching 85% in cycle II. The conclusion of this study is that the application of the PBL model with the CRT approach is effective in improving student learning outcomes.